Alternative sources of supplements in Africanized honeybees submitted to royal jelly production - doi: 10.4025/actascianimsci.v35i2.16976 - Sereia, Maria Josiane; Toledo, Vagner de Alencar Arnaut de; Furlan, Antonio Claudio; Faquinello, Patrícia; Costa-Maia, Fabiana Martins; Wielewski, Priscila (Acta Scientiarum. Animal Sciences, 2012)
This study was carried out to evaluate the effect of supplements with isolated soy protein, brewer’s yeast, a mixture of isolated soy protein with brewer’s yeast, linseed oil, palm oil and mixture of linseed oil with palm oil in the royal jelly production of Africanized honey bee colonies. Total royal jelly produced was superior (P < 0.05) in colonies that were fed with isolated soy protein and brewer’s yeast (11.68g/colony), followed by linseed oil and palm oil (11.30g/colony) and palm oil (9.61g/colony), and the latter higher than controls I (6.35g/colony), and II (6.95g/colony). Thus, mixed supplements are viable to optimize this beekeeping activity in commercial scale.